The Effect of Service Quality on Customer Satisfaction with Trust as a Mediator - Luh Putu Nevi Widiastuti; Dwi Orbaningsih; Bhakti Hendrakusuma (LPPM STIE KRAKATAU, 2026)
This study aims to examine the effect of service quality on customer satisfaction with trust as a mediating variable at PT BPD Bali’s Singaraja Branch. Service quality was measured using the five SERVQUAL dimensions: tangibility, reliability, responsiveness, assurance, and empathy. A quantitative explanatory approach was applied using data from 400 customers selected through accidental sampling method. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all service quality dimensions significantly affect trust and the customer satisfaction. Tangibility and empathy were the strongest predictors of trust, whereas reliability had the strongest direct effect on satisfaction. Trust also significantly influenced satisfaction and partially mediated the relationship between service quality and satisfaction. The model explained 59.7% of the trust variance and 50.8% of the satisfaction variance. The study concludes that improving service quality is essential for enhancing customer satisfaction directly and indirectly through trust. Banks should prioritize reliable, responsive, and customer-oriented services to strengthen their long-term relationships. This study contributes to the banking service literature by extending the SERVQUAL model through trust as a mediating mechanism in regional banking. However, the study was limited to one branch and cross-sectional data, which may reduce generalizability. Future studies should involve multiple institutions and additional variables, such as digital service quality and loyalty.